2017
DOI: 10.1080/24694193.2017.1386969
|View full text |Cite
|
Sign up to set email alerts
|

Heat Loss Prevention Education Aids Nurses’ Knowledge in Prevention of Hypothermia in Newborns

Abstract: Newborns are at risk of developing hypothermia due to the instability of their thermoregulation systems and inability to adjust to changes in ambient temperature. This risk increases during hospitalization. Education is a strategy to improve nurses' understanding of the prevention of hypothermia in newborns in the hospital. This study aimed to analyze the impact of education about preventing heat loss on nurses' knowledge and behavior in preventing hypothermia in newborns. The study design was a quasi-experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This study coincided with a study by Purnamasari et al who evaluated the momentous improvement in nurses' knowledge in prevention of hypothermia in newborns after heat loss prevention education. 17 The results of this study are in line with those found by Chang et al, 18 which appraised significant improvement in nurses' knowledge after an information program about thermoregulation in neonates was provided.…”
Section: Discussionsupporting
confidence: 90%
“…This study coincided with a study by Purnamasari et al who evaluated the momentous improvement in nurses' knowledge in prevention of hypothermia in newborns after heat loss prevention education. 17 The results of this study are in line with those found by Chang et al, 18 which appraised significant improvement in nurses' knowledge after an information program about thermoregulation in neonates was provided.…”
Section: Discussionsupporting
confidence: 90%
“…Although further research is needed, it can be speculated that increased nurse knowledge and commitment provide an essential return on investment through nurse education. Preventing hypothermia complications such as intraventricular hemorrhage and respiratory distress by improving nursing knowledge and assessment of hypothermia in infants may impact outcomes (Purnamasari et al, 2017; Verklan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Pretest and posttest scores were compared using a paired t test before and after the educational activity (see Table 1). The self-evaluation of nurse commitment to improved practice was assessed after the educational activity (Polit & Beck, 2017; Purnamasari et al, 2017). See Supplemental Digital Content 3 (http://links.lww.com/JNPD/A39) for the nursing self-evaluation survey.…”
Section: Methodsmentioning
confidence: 99%
“…Education on prevention of heat loss has been shown to be an effective strategy to promote nurses' knowledge and behavior in preventing hypothermia. 27 Furthermore, targeted interventions for larger infants should be developed and tested to prevent the onset of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…To decrease and eliminate costly and preventable admissions to the NICU, future implications for research should focus on identifying potential risk factors for developing hypothermia in not only infants less than 1500 g but also those born 1500 g or more. Education on prevention of heat loss has been shown to be an effective strategy to promote nurses' knowledge and behavior in preventing hypothermia 27. Furthermore, targeted interventions for larger infants should be developed and tested to prevent the onset of hypothermia.…”
Section: Discussionmentioning
confidence: 99%